Advanced methods for partitioned fluid-structure interaction simulations applied to ship propellers - Lund, Jorrid; Radtke, Lars; Düster, Alexander; Ferreira Gonzalez, Daniel; Abdel-Maksoud, Moustafa (The American Society of Mechanical Engineers, 2022)
In naval architecture, fluid-structure interaction (FSI) is highly important for many applications. The accurate and fast computation of FSI problems is for this reason a major challenge for a simulation engineer working on flexible structures interacting with water and wind. For ship propellers, steel and metal alloy have long been the dominating choice of material. With the advancement in the development of fiber-reinforced polymers such as carbon fiber reinforced polymers the consideration of FSI for ship propellers becomes increasingly important. This work presents a partitioned coupled solution approach for the simulation of FSI problems on the example of a large ship propeller. The in-house developed software library comana is used as coupling manager together with the commercial finite element method solver ANSYS as structural solver and the boundary element method solver panMARE as fluid solver. comana offers the possibility to couple a number of existing and highly specialized solvers to solve multifield problems. For partitioned coupled FSI problems the increased computational effort due to the necessary coupling iterations and possible instabilities due to the partitioned coupling should be reduced by suitable predictor and convergence acceleration methods. For convergence acceleration, the Aitken method is one of the most common choices even though Quasi-Newton methods such as the Quasi-Newton least-squares method show promising results for the acceleration of FSI simulations. The interpolation technique which is necessary to map the coupling quantities between the subfields for a nonmatching discretization on the interface between the subproblems is also important for a stable, accurate, and fast solution. The simulation of a ship propeller is introduced and the advantages and disadvantages of the partitioned FSI simulation approach are shown. Predictor and convergence acceleration schemes to improve the solution process are discussed and results for flexible ship propellers are presented. ...